Expression patterns of MRP2 in circulating tumor cells of breast cancer: a single-institution study - Guan, Jiayu; Li, Fuping; Zhou, Wenbin (Frontiers in Oncology, 2025)
BackgroundBreast cancer metastasis remains a major oncology challenge, with circulating tumor cells (CTCs) driving dissemination and multidrug resistance (MDR) hindering treatment efficacy. MRP2, an ABC transporter linked to MDR, may promote CTC survival; however, its expression in CTCs and its association with epithelial-mesenchymal transition (EMT) in breast cancer remain underexplored.Materials and methodsA total of 52 breast cancer patients were recruited for the study, from whom circulating tumor cells (CTCs) were isolated from 5 ml of peripheral blood samples utilizing the CanpatrolTM CTC detection platform. Subsequently, a comprehensive multiple mRNA in situ analysis (MRIA) employing diverse molecular markers was conducted to accurately identify and categorize CTCs. The relationships between CTC counts, subtypes (epithelial type, E type; hybrid epithelial/mesenchymal type, H type; mesenchymal type, M type), and MRP2 expression in CTCs were analyzed using Spearman’s correlation coefficient. Statistical analyses were performed using the SPSS software.ResultsCTCs were detected in 94.2% of patients. H-type CTCs and MRP2 (+) CTCs were significantly associated with larger tumor size (P < 0.05). MRP2 expression was higher in (H+M)-type than in E-type CTCs (P < 0.001). EMT grade was positively correlated with MRP2 (+) CTCs grade and high MRP2 expression (R = 0.283, P = 0.042), with strong correlations between all CTC subtypes and MRP2 expression.ConclusionThis study pioneers the MRP2-CTCs-EMT axis in breast cancer, clarifying MRP2’s role in CTC biology and EMT, providing a theoretical basis for combined targeting strategies to improve metastatic breast cancer management.